US Budget Impact Model for Selinexor in Relapsed or Refractory Multiple Myeloma - Bassali J; Gould IG; Kaye JA; Mladsi D; Mehta J (Dove Medical Press, 2020)
Jan Bassali, 1 Ian Gopal Gould, 2 James A Kaye, 3 Deirdre Mladsi, 4 Jyotsna Mehta 5 1Global Medical and Scientific Affairs Department , Karyopharm Therapeutics, Newton, MA, 02459, USA; 2Research Health Economy, RTI Health Solutions, Research Triangle Park, NC 27709-2194, USA; 3Epidemiology, RTI Health Solutions, Research Triangle Park, NC, USA; 4Health Economics - Strategy and Early Modeling, RTI Health Solutions, Research Triangle Park, NC, USA; 5HEOR, Karyopharm Therapeutics, Newton, MA 02459, USACorrespondence: Jan BassaliKaryopharm Therapeutics, Newton, MA 02459, USATel +1 617 658-0600Email jbassali@karyopharm.comObjective: To estimate the budgetary impact of adopting selinexor (XPOVIO; Karyopharm Therapeutics, Inc.) for the treatment of adult patients with penta-refractory multiple myeloma (MM) from the perspective of a third-party payer in the United States (US).Methods: A budget impact analysis was conducted in one-year increments for the first 3 years after the introduction of selinexor for a private payer or Medicare Part D. Total annual treatment costs (2018 US dollars) were calculated as the sum of drug costs, costs of adverse events (AEs; grade ≥ 3), along with ongoing best supportive care costs. The number of eligible patients was derived from national epidemiology statistics, healthcare databases, and published literature.Results: In the base-case analysis, selinexor was associated with a per member per month (PMPM) cost of $0.0103 in year 3, assuming a market uptake of 64%, for a hypothetical private payer plan with one million members and four eligible patients. In a scenario analysis with 16 eligible patients with triple-class refractory MM regardless of the line of therapy (this additional scenario analysis was performed with an eligible population that does not fit squarely within the approved label for selinexor but was performed strictly for the purpose of demonstrating the results of the budget impact model when based on a larger pool of  eligible patients), the estimated PMPM cost in year 3 was $0.0388. The model showed comparable sensitivity to treatment duration, wholesale acquisition cost for selinexor, and year 1 uptake. The base-case analysis conducted from the perspective of Medicare Part D was associated with a PMPM cost of $0.0078 in year 3 with 159 eligible patients.Conclusions: The model estimates a small and manageable budget impact of adopting selinexor into a third-party US payer plan, given the low prevalence of penta-refractory MM.Keywords: multiple myeloma, budget impact analysis, Selinexor, US